Palladium-Catalyzed Asymmetric 1,4-Addition of Diarylphosphines to α,β-Unsaturated Sulfonyl Fluorides - Cheng, An-Qi; Wu, Zeng-Hua; Yang, Huai-Lan; Duan, Wei-Liang (Synthesis, 2023)
A Pd-catalyzed asymmetric phosphination of α,β-unsaturated sulfonyl fluorides was developed, and a series of tertiary phosphorus compounds were obtained in excellent yields and enantioselectivities (up to 99% ee). The chiral adduct can be further converted into chiral phosphine sulfonic acid as the ligand for the arene Ru metal complex.
Keywords: α,β-unsaturated sulfonyl fluoride; asymmetric 1,4-addition; palladium catalyst; chiral phosphine